2021
DOI: 10.1073/pnas.2105154118
|View full text |Cite
|
Sign up to set email alerts
|

Ion correlations drive charge overscreening and heterogeneous nucleation at solid–aqueous electrolyte interfaces

Abstract: Classical electrical double layer (EDL) models are foundational to the representation of atomistic structure and reactivity at charged interfaces. An important limitation to these models is their dependence on a mean-field approximation that is strictly valid for dilute aqueous solutions. Theoretical efforts to overcome this limitation are severely impeded by the lack of visualization of the structure over a wide range of ion concentration. Here, we report the salinity-dependent evolution of EDL structure at n… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

10
82
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
9
1

Relationship

1
9

Authors

Journals

citations
Cited by 56 publications
(92 citation statements)
references
References 51 publications
10
82
0
Order By: Relevance
“…Based on the experimental data for the capacitance of a mercury electrode in contact with an aqueous electrolyte solution, Watts-Tobin and Mott predicted additional contributions to the capacitance due to the adsorption of mercury atoms and charge transfer at the electrode–electrolyte interface and due to the reduction of the dielectric constant of water in the inner region of the EDL. , More recent experiments and theoretical analyses provide direct evidence that solvent molecules, water in particular, are highly organized near a charged surface . The local electric field reduces the molecular polarizability while elevating the average density in comparison to those in the bulk solution, which may lead to a negative capacitance. , Besides, the chemisorption of ionic species results in changes in the electronic structure of the electrode that cannot be faithfully described by conventional surface reaction models yet are important for understanding nonclassical charging behavior including negative double-layer capacitance and pseudocapacitance. ,, As the electrolyte concentration increases, the EDL structure exhibits a transition from the Langmuir-type charge compensation to nonclassical charge overscreening and alternative layering of cations and anions . The electrified surface may induce the nucleation of nanocrystals at a threshold concentration that is significantly lower than the bulk solubility limit.…”
Section: Introductionmentioning
confidence: 99%
“…Based on the experimental data for the capacitance of a mercury electrode in contact with an aqueous electrolyte solution, Watts-Tobin and Mott predicted additional contributions to the capacitance due to the adsorption of mercury atoms and charge transfer at the electrode–electrolyte interface and due to the reduction of the dielectric constant of water in the inner region of the EDL. , More recent experiments and theoretical analyses provide direct evidence that solvent molecules, water in particular, are highly organized near a charged surface . The local electric field reduces the molecular polarizability while elevating the average density in comparison to those in the bulk solution, which may lead to a negative capacitance. , Besides, the chemisorption of ionic species results in changes in the electronic structure of the electrode that cannot be faithfully described by conventional surface reaction models yet are important for understanding nonclassical charging behavior including negative double-layer capacitance and pseudocapacitance. ,, As the electrolyte concentration increases, the EDL structure exhibits a transition from the Langmuir-type charge compensation to nonclassical charge overscreening and alternative layering of cations and anions . The electrified surface may induce the nucleation of nanocrystals at a threshold concentration that is significantly lower than the bulk solubility limit.…”
Section: Introductionmentioning
confidence: 99%
“…A charged interface commonly exists in nature and in biological systems and is responsible for heterogeneous processes and interfacial phenomena important in many geological, environmental, electrochemical, biological, and industrial systems. Using electric field induced (EFI) second harmonic generation (SHG) or sum-frequency generation vibrational spectroscopy (SFG-VS), one can directly measure the potential changes across the charged interfaces through the bulk third-order nonlinear susceptibility (χ (3) ) mechanism first demonstrated by Eisenthal et al in the early 1990s. The two typical charged interface systems studied were the silica/water interface and the charged Langmuir monolayer covered air/water interface. It was successfully shown that the second harmonic field responses from those interfaces are linearly dependent on the interfacial electric potential, making it possible to directly and quantitatively study the electrolyte concentration effects and acid–base equilibrium at the charged aqueous interfaces. …”
Section: Introductionmentioning
confidence: 99%
“…Water is one of the most important substances [1,2,3,4] and water/oxide interfaces are ubiquitous on earth, playing important roles in numerous chemical, physical, geological, and biological processes, [5,6,7,8] such as mineral degradation, [9,10] heterogeneous catalysis, [11] phase transitions, [12] solute adsorption [13,14] and wetting. [15,16] Investigating the behavior of interfacial waters is essential to help the design and development of better materials to overcome the energy crisis or increase their biological compatibility.…”
Section: Introductionmentioning
confidence: 99%